The Effectiveness of Using Media Jeopardy Game Towards Studentsâ€™ English Grammar Skill â€œSimple Present Tenseâ€ of Seventh Grade Class At Smps Plus Kasih Ibu Patumbak Academic Year 2022/2023 - Ila Paramida; Zulfitri Zulfitri (Universitas Negeri Medan, 2023)
Nowdays, there are still many students have difficulty in mastering some terms of simple present tense, such as in understanding why some sentences used auxiliaries, is, am, and are, they also confuse in understanding â€“s/-es addition of verbs and the use of do/does in Interrogative sentence. The purpose of this research is to know Jeopardy game give effect or not in learn simple present tense. The method of this research was quantitative research method.Â The sample of this research consisted of 35 students of 7A the experimental class and 35 students of 7C as the control class. From the data that has been analyzed, the researcher found that the mean of the post-test result of experimental class is 30,28, while the mean of the post-test result of control class is 25,48. The result of computing the t-test shows that the t- observed is higher than t-table or it can be showed as follow: t-observed is 1,8 and t-table is 0.05. It means that t-observed is the higher than t-table (1,8<0.05) with df 68 at the level of significance a=0,025. Thus, the alternative hypothesis (Ha) is accepted. It can conclude that in the teaching and learning process by using Jeopardy Strategy in simple present tense text is effective to use.